LUKA DI KEPALA PADA PENGENDARA SEPEDA MOTOR AKIBAT KECELAKAAN LALU LINTAS DI BANDUNG - Bari Sailendra, Agus
Abstract: The number of reported road accidents in Indonesia during the last decade (1980-1990) has dropped by about 49 per cent, while the number of reported of fatalities has remained fairly constant at about 10,000 deaths per year. To compare with other countries Indonesia has fatality rates per 10,000 vehicles at least 6 times higher than those in developed countries; 34 per cent of those killed in traffic accidents were motorcycle riders. In Bandung (1990), 43% of those injured casualties in road accidents were motoryclists. Since the mid 1980\'s, the Police has tried to improve the safety of motorcyclists by introducing the wearing of helmets. The objectives of this study were (1) to quantify the number of motorcycle rider head injuries caused by traffic accidents, (2) to relate the incidence of head injuries to helmet wearing levels, and (3) to determine the potential benefit of wearing helmets properly in Indonesia. The study was conducted in the City of Bandung and based on traffic accident data in the Traffic Police Headquarters (Triple-L) for the period 1989-1993, Medical Record in The RSHS for 1991-1993, and purposely colected data from Emergency Unit Service (EmU) of RSHS during 45 days (February-March 1994). Also helmet wearing levels were surveyed on nine road links for three hours each at peak periods. The assumption was that helmets were standard. The hypotheses were (1) Percentage of fatalities and serious casualties (3-L & EmU) should be lower for riders who wore helmets than those who did not. (2) The wearing levels of head injured casualties should be less than those observed in street surveys. The results indicated that more than one-third of traffic accident casualties were motorcyclists and about 56% of these were killed or seriously injured. About 40% of these the casualties suffered head injuries. Field surveys and other data showed that more than 85% wore helmets but only about one-half (42%) wore helmets correctly. Statistical tests showed that there were no differences between helmet wearers and non-wearers at 5% level of significance, ie wearers were not more likely to die or suffer head injuries than non-wearers. So, the wearing of helmets at the time had no safety benefit. However, there were significant differences in the wearing level estimates obtained from different data sets.